The wolf of Wall Street [videorecording (DVD)] - DiCaprio, Leonardo; Hill, Jonah, 1983-; Robbie, Margot, 1990-; McConaughey, Matthew, 1969-; Chandler, Kyle; Reiner, Rob; Favreau, Jon; Dujardin, Jean, 1972-; Lumley, Joanna; Ebersole, Christine; Bernthal, Jon; Whigham, Shea, 1969-; et al.
Sex. Money. Power. Drugs. Brace yourself for an outrageous true story from legendary filmmaker Martin Scorsese. Jordan Belfort, a young stockbroker, is hungry for fame and glory in New York City, where corruption is king and more is never enough.